2018
DOI: 10.1007/s10461-018-2356-2
|View full text |Cite
|
Sign up to set email alerts
|

HIV Physicians and Chronic Opioid Therapy: It’s Time to Raise the Bar

Abstract: Clinical practice that utilizes chronic opioid therapy has been recognized as one major cause of the opioid crisis. Among patients living with HIV, the risks associated with chronic opioid therapy may be complicated by factors such as co-occurring mental health diagnoses, substance use, and economic marginalization. Improving opioid prescribing practices in HIV clinics requires attention to these and other characteristics common to HIV care. In the context of a randomized controlled trial testing an interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Whether and how the observed immunosuppressive effects of prescribed opioids result in increased risk of other adverse outcomes, such as malignancy, merits investigation. In addition, enhanced efforts to decrease opioid prescribing(72) while promoting access to indicated treatments for pain (73) and opioid use disorder (74) in HIV treatment settings are urgently needed (75)(76)(77).…”
Section: Medication Classes Of Particular Concern Among Pwhmentioning
confidence: 99%
“…Whether and how the observed immunosuppressive effects of prescribed opioids result in increased risk of other adverse outcomes, such as malignancy, merits investigation. In addition, enhanced efforts to decrease opioid prescribing(72) while promoting access to indicated treatments for pain (73) and opioid use disorder (74) in HIV treatment settings are urgently needed (75)(76)(77).…”
Section: Medication Classes Of Particular Concern Among Pwhmentioning
confidence: 99%
“…While some of this opioid use may reflect use of prescribed opioids (i.e., provided by a clinician) for treatment of pain, findings from the Medical Monitoring Project (MMP), a national surveillance study of PWH, demonstrated that 3% of the sample had extra-medical opioid use largely driven by extra-medical prescription opioids use. 26 Given these data from the MMP combined with those from other studies 24,25,48,61 and a clinical context where opioid prescribing practices have been slowly changing, 62 our data raise concern that a substantial number of individuals are exposed to opioids and at risk for escalating opioid use. This is concerning as opioid use, and particularly a pattern of escalating use, is likely associated with greater potential harms, including falls, 63 infectious complications, 46 addiction, and overdose.…”
Section: Factors Associated With Opioid Use Trajectory Groupmentioning
confidence: 74%
“…12,14 Release of guidelines for opioid prescribing by the Centers for Disease Control and Prevention and Infectious Diseases Society of America 17,74 have stimulated more careful opioid prescribing. 62 Whether nonopioid psychoactive medication duration is a marker of symptom severity, treatment initiation or lack of response, or itself serves to promote escalating opioid use warrants further investigation. Regardless, these findings are concerning given that these medications may also be used extramedically to promote euphoria and/or recover from opioid use, 48,49 and in combination with opioids these drugs may contribute to risk of adverse events, particularly overdose.…”
Section: Factors Associated With Opioid Use Trajectory Groupmentioning
confidence: 99%
“…7,52 However, adopting LTOT guidelines is challenging for HIV providers. 53 They report low levels of satisfaction for pain management aspects of clinical care, as well as low confidence in their abilities to treat chronic pain. 54,55 Few physicians follow standard protocol regarding assessment and may lack resources to closely monitor patients, [55][56][57][58][59][60] resulting in wide variation in opioid prescribing patterns, similar to primary care.…”
Section: Introductionmentioning
confidence: 99%